Building a Total Quality Management Model for Healthcare Industry - ., Jonny; Yuri M. Zagloel, T (International Journal of Engineering and Technology, 2018)
This paper is made to present a Total Quality Management (TQM) Model for Healthcare Industry for Indonesia. From previous study, there are nine Total Quality Management (TQM) practices in healthcare industry such as Top Management Commitment (TMC), Teamwork and Participation (TWP), Process Management (PM), Customer Focus and Satisfaction (CFS), Resource Management (RM), Organizational Behavior and Culture (OBC), Continuous Improvement (CI), Training and Education (TE) and Information Management (IM) . However, these practices are not integrated yet. Therefore, this paper aims to integrate these practices by applying Structural Equation Modeling (SEM). After administering about 200 questionnaires using Linear Structural Relations (LISREL) program, the p-value is at 0.45 above required 0.05 giving the meaning that the model is good fit. This signifies that these nine TQM practices are required to achieve goals of the industryÂ Â